Plasma turbulence in localized sheared flows - Chirkov, A.Yu (Вопросы атомной науки и техники, 2007)
Plasma configurations with strong velocity shear are considered taking into account magnetic shear. Ion temperature gradient driven drift instability and Kelvin-Helmholtz type instability are analyzed for such sheared plasma flows. Possible instability saturation mechanisms and estimation of particle diffusivity are discussed. Розглядаються плазмові конфігурації із сильним широм швидкостей, а також з обліком магнітного шира. Для таких течій плазми аналізуються іонно-температурно-градієнтна нестійкість і нестійкість типу Кельвіна-Гельмгольца. Обговорюються механізми насичення нестійкостей і оцінки коефіцієнта дифузії. Рассматриваются плазменные конфигурации с сильным широм скоростей, а также с учетом магнитного шира. Для таких течений плазмы анализируются ионно-температурно-градиентная неустойчивость и неустойчивость типа Кельвина-Гельмгольца. Обсуждаются механизмы насыщения неустойчивостей и оценки коэффициента диффузии.